A child at gunpoint - Raskin, Richard (Aarhus Univ. Press, 2004)
A close look at the photograph – The origins of the photo : The Stroop Report – The photograph in context – Identities – The role of the photograph in selected works of art – Palestinian parallels? : uses of the photo in a war of images.
9788779340992
Keywords: Holocaust; Jewish (1939-1945); Photography; Holocaust; Jewish (1939-1945); in art; Documentary photography; Holocaust; Jewish 1939-1945; Holocaust; Jewish 1939-1945; in art